Comments on cladocerans of crater lakes of the Nevado de Toluca Volcano (Central Mexico), with the description of a new species, Alona manueli sp. nov. - Sinev, Artem Y.; Zawisza, Edyta (Zootaxa, 2013)
Cladoceran communities of two lakes of Nevado de Toluca Volcano, Central Mexico, were studied. A new species of Aloninae, Alona manueli sp. nov., is described. It was previously confused with Palearctic Alona intermedia Sars, 1862, but clearly differs from it in the morphology of postabdomen, head shield and head pores, and thoracic limbs. Position of Alona manueli sp. nov. within the genus is unclear, it did not belong to any species-group within Alona s. lato. Other spe-cies recorded in the studied lakes are Alona ossiani Sinev, 1998, Alonella pulchella Herrick, 1884, Chydorus belonging to sphaericus-group, Eurycercus longirostris Hann, 1982 and Pleuroxus cf. denticulatus Birge, 1879.